The influence of design, ambient factors, and social interaction in food truck settings on visitors’ perceptions (BIS Humanities and Social Science, 2026)
Food trucks have recently emerged as a prominent trend across a wide range of events, from culinary festivals to public gatherings. As a growing sector within the culinary industry, food truck design must balance operational efficiency with a supportive working environment. Understanding current food truck conditions is therefore essential for mapping both the physical and psychological needs of visitors. While previous studies have primarily examined layout and workflow from an employee operational standpoint, limited attention has been given to the psychological environment that shapes visitor experience. This research employs a quantitative approach using questionnaire-based visitor responses to capture perceptual evaluations without predicting or manipulating behavioral outcomes. The study began with interviews and field observations, followed by a main questionnaire in which research stimuli were presented as dependent variables and visitor perceptions of Bandung food trucks served as independent variables. Collected data were categorized and analyzed to identify key perceptual drivers. The findings indicate that design variables particularly color and form are the most significant factors influencing visitor perception, with color receiving 64% “strongly agree” and 36% “agree,” and form receiving 50% “agree,” 25% “strongly agree,” and 25% “abstain.” The implications of these findings highlight the need for food truck operators to prioritize visual coherence, brand-aligned color strategies, and well-articulated vehicle forms to enhance perceived quality and increase purchase intention. Additionally, understanding perceptual factors can guide designers and policymakers in shaping more user centered mobile culinary environments that support both commercial effectiveness and visitor comfort.